2014
DOI: 10.5688/ajpe789167
|View full text |Cite
|
Sign up to set email alerts
|

An Educational Program for Underserved Middle School Students to Encourage Pursuit of Pharmacy and Other Health Science Careers

Abstract: Objective. To develop and implement an active, hands-on program for underrepresented minority (URM) seventh grade students and to determine if participation in the program increased interest in health care careers and understanding of pharmacy and physician assistant (PA) professions. Design. A hands-on educational program was developed in conjunction with local middle school administrators and staff for URM 7th grade students. The program was designed to be hands-on and focus on pharmacy and PA laboratory ski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…The current shortage of graduates in the fields of Science, Technology, Engineering and Mathematics (STEM) calls for new strategies to promote students' choice of STEM careers (Fox & Hackerman 2002;Lee 2015;Wang 2013a). Since this choice was found to be strongly influenced by students' achievement in STEM disciplines (Goldsmith, Tran & Tran 2014;Nugent, Barker, Grandgenett & Adamchuk 2010), their self-efficacy beliefs in STEM (Maltese & Tai 2011;Wang 2013b) and personal interest (Hall, Dickerson, Batts, Kauffman & Bosse 2011), educational reforms should target these features. A promising approach in this regard, is the use of an integrated curriculum (Czerniak, Weber, Sandmann, & Ahern 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The current shortage of graduates in the fields of Science, Technology, Engineering and Mathematics (STEM) calls for new strategies to promote students' choice of STEM careers (Fox & Hackerman 2002;Lee 2015;Wang 2013a). Since this choice was found to be strongly influenced by students' achievement in STEM disciplines (Goldsmith, Tran & Tran 2014;Nugent, Barker, Grandgenett & Adamchuk 2010), their self-efficacy beliefs in STEM (Maltese & Tai 2011;Wang 2013b) and personal interest (Hall, Dickerson, Batts, Kauffman & Bosse 2011), educational reforms should target these features. A promising approach in this regard, is the use of an integrated curriculum (Czerniak, Weber, Sandmann, & Ahern 1999).…”
Section: Introductionmentioning
confidence: 99%
“…6 A literature review by the committee revealed that early education about the pharmacy profession aimed at high school students and parents may be helpful; however, they found limited data to document the effectiveness of particular initiatives. [7][8][9][10] In addition to strategies aimed at increasing the pipeline, short-term strategies aimed at improving admission processes and attracting and retaining applicants already interested in the pharmacy program is another approach. Building authentic relationships with applicants and increasing touchpoints after a student has been admitted are proactive steps to maximize admission yield and minimize summer "melt."…”
Section: Introductionmentioning
confidence: 99%
“…In a pre–post study by Goldsmith et al . (2014) , students were given a survey about interest in healthcare careers and knowledge about health professions in the context of a career education program.…”
Section: Introductionmentioning
confidence: 99%